The economic crisis in the euro area - CHIRIMBU, Sebastian; BURDA, Alexandru (Annals of Spiru Haret University. Economic Series, 2011)
The article proposes an analysis of some European financial markets on the background of the recent crisis, markets that have become very alarmed by the increase of the Euro States’ budget deficits and the possible entry of some of them in a situation of not being able to pay rates on debts contracted by the Government. Such imbalances can be avoided in general either by a correct evaluation or by a controlled devaluation of national currencies, or by means of the exchange rates of various currencies. However, in the Euro area, this is not possible due to the very existence of a single currency, a context in which the authors suggest the use of alternative solutions.